Exploring the disparity between inflammation and disability in the 10-year outcomes of people with rheumatoid arthritis. (11th March 2022) - Gwinnutt, James M; Norton, Sam; Hyrich, Kimme L; Lunt, Mark; Combe, Bernard; Rincheval, Nathalie; Ruyssen-Witrand, Adeline; Fautrel, Bruno; McWilliams, Daniel F; Walsh, David A; Nikiphorou, Elena; Kiely, Patrick D W; et al.
Abstract: Objectives: To identify groups of people with RA with different disability trajectories over 10 years, despite comparable levels of inflammation. Methods: Data for this analysis came from three European prospective cohort studies of people with RA [Norfolk Arthritis Register (NOAR), Early RA Network (ERAN), Étude et Suivi des Polyarthrites Indifférenciées Récentes (ESPOIR)]. Participants were assessed regularly over 8 (ERAN) to 10 (NOAR/ESPOIR) years. Inclusion criteria were: recruited after 1 January 2000, <24 months baseline symptom duration, and disability (HAQ) and inflammation [two-component DAS28 (DAS28-2C)] recorded at baseline and at one other follow-up. People in each cohort also completed patient-reported outcome measures at each assessment (pain, fatigue, depressive symptoms). Group-based trajectory models were used to identify distinct groups of people with similar HAQ and DAS28-2C trajectories over follow-up. Results: This analysis included 2500 people with RA (NOAR: 1000, ESPOIR: 766, ERAN: 734). ESPOIR included more women and the participants were younger [mean (standard deviation) age: NOAR: 57.1 (14.6), ESPOIR: 47.6 (12.5), ERAN: 56.8 (13.8); women: NOAR: 63.9%, ESPOIR: 76.9%, ERAN: 69.1%). Within each cohort, two pairs of trajectories following the hypothesized pattern (comparable DAS28-2Cs but different HAQs) were identified. Higher pain, fatigue and depressive symptoms were associated with increased odds of being in the high HAQ trajectories. Conclusion: Excess disability is persistent in RA. Controlling inflammation may not be sufficient to alleviate disability in all people with RA, and effective pain, fatigue and mood management may be needed in some groups to improve long-term function.